2012
DOI: 10.1186/1752-153x-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Tracking antioxidant properties and color changes in low-sugar bilberry jam as effect of processing, storage and pectin concentration

Abstract: Background: Recently, an increased interest in the identification of valuable possibilities for preserving the antioxidant properties of products obtained by thermal processing of fruits rich in bioactive compounds can be noticed. In this regard, an extensive analysis is necessary in terms of thermal processed products behavior in relation to various factors. The purpose of the present study was to assess the effect which processing and storage at 20°C has on the antioxidant properties and color quality of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
27
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 37 publications
10
27
3
2
Order By: Relevance
“…These results are in agreement with [50] [64] reported that vitamin C decreased in low calorie jam during storage. The loss of vitamin C in the initial stages is because of the presence of oxygen in the headspace or this could due to oxidation or degradation of the thermolabile ascorbic acid into dehydrate ascorbic acid upon storage [64].…”
Section: Vitamin C and Total Soluble Solids Contentssupporting
confidence: 83%
“…These results are in agreement with [50] [64] reported that vitamin C decreased in low calorie jam during storage. The loss of vitamin C in the initial stages is because of the presence of oxygen in the headspace or this could due to oxidation or degradation of the thermolabile ascorbic acid into dehydrate ascorbic acid upon storage [64].…”
Section: Vitamin C and Total Soluble Solids Contentssupporting
confidence: 83%
“…Antioxidant compounds such as flavonoids, tocopherols, catechins, carotenoids, etc., are able to degrade ROS, which is known as antioxidant capacity [14,15]. Antioxidant compounds are present in In contrast to what was observed, Figure 2 shows that fertilizer concentration had a significant effect on the fresh weight of coriander plants, while the mixture of substrates and the interaction between factors had no effect.…”
Section: Evaluation Of Antioxidant Capacitycontrasting
confidence: 47%
“…Antioxidant compounds such as flavonoids, tocopherols, catechins, carotenoids, etc., are able to degrade ROS, which is known as antioxidant capacity [14,15]. Antioxidant compounds are present in plants [16] and are important protective agents for human health; thus, the presence of these compounds provides an added value to food products and is one of the characteristics sought in functional foods.…”
Section: Evaluation Of Antioxidant Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are also some studies which have reported an antioxidant effect in vitro, but not in vivo [41]. Moreover, the strawberry variant and temperature conditions are also important factors in the loss of antioxidants content [33,34].…”
Section: Discussionmentioning
confidence: 99%